(untitled) (International Journal of Engineering and Computer Science, 2016)
There are many devices present which help to interact with the computer like a mouse, keyboard, and mice. Those devices also called as Human Computer Interaction (HCI) device. Our main intention is to develop Human Computer Interaction device to use efficiently .Where we have tried to control mouse event like left click, right click and moving pointer position using the color detection. The color detection is done using the web camera.